Evaluating Character Education in Sekolah Penggerak Senior High Schools: Implications for Global Competitiveness - Fitri Kumala Dewi; Siti Ubaidah; Meirisa Sahanata; Hedia Rizki; Sunarto (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
Character education is widely recognized as a crucial element in enhancing educational quality in an increasingly competitive global context; however, evaluative studies that specifically investigate its implementation within the Sekolah Penggerak Program at the senior high school level remain limited. This study aims to evaluate the implementation of character education in the Sekolah Penggerak Program and to examine its outcomes and impact on students’ character development. An evaluative research approach was employed using the CIPPO model. The research was conducted at State Senior High Schools 4, 5, and 10 in Jambi City, involving principals or vice principals, teachers, and students as research participants. Data were collected through questionnaires and semi-structured interviews. Questionnaire data were analyzed using descriptive percentage analysis, while interview data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The results reveal that character education has been implemented in a systematic and integrated manner through school policies, instructional practices, and school culture, with most achievement indicators classified as high to very high. Furthermore, the implementation contributes positively to students’ character development, particularly in the areas of integrity, discipline, collaboration, critical thinking, and digital literacy, thereby supporting improvements in educational quality aligned with contemporary global demands.